History's mysteries Disc 2 Disc two. Ghost Ships : Nazi Ghost Train - Kent, Arthur, 1953-; Ackroyd, David; Arts and Entertainment Network; A & E Home Video (Firm); New Video Group; History Channel (Television network) (New York, N.Y. : A & E Television Networks : Distributed by New Video Group, 2011)
Pick up where the textbooks leave off with History's mysteries and explore the stories, events, legends, and myths that have aroused curiosity, inspired wonder, and incited debate throughout the ages.
Disc two contains episodes: Ghost ships; Nazi ghost train.
Ghost ships -- Nazi ghost train.
Originally broadcast as a segment of the series History's mysteries.
Title on spine and discs: Classics.
Title from container.
Executive producers, Robb Weller, Gary H. Grossman ; produced by John Joseph.
Arthur Kent, host ; David Ackroyd, narrator.
DVD, Dolby digital sound.
Keywords: Haunted places; Psychics -- United States -- Biography; Ghosts; Atlantic Ocean -- Bermuda Triangle; Biographies; Television programs